Investigation of sand-geomaterial interface response using fractal theory: particle shape, gradation and surface roughness effects - Ari, Abdulmuttalip; Akbulut, Suat (ELSEVIER, 2025)
The geometric properties of sand and geomaterials are considered to be the main factors affecting the interface response. The quantitative characterization of geometric parameters will enhance the engineering understanding of the interfaces. In this study, quantification of particle shape, gradation, and surface roughness parameters was performed with fractal geometry approach inspired by the irregular structures of the material geometries. The interface shear analyses were conducted to determine peak, residual interface friction and dilation angles, coordination number, and contact anisotropy using discrete element numerical method. The analysis parameters were calibrated with the experimental results of a custom-made transparent interface shear box using digital image processing. The analysis results show that the interface friction and dilation angles increase with increasing fractal dimension of particle shape and surface roughness. However, the friction angle exhibits a bell-shaped distribution with the change of the gradation fractal dimension. Moreover, the effect of the gradation fractal dimension on the friction angle differs depending on the roughness level. The rate of contact loss and contact anisotropy follow similar trends to the interface friction angle with changes in fractal dimensions. Considering the fractal dimension of the material geometries, macro and micro scale interface responses were defined and the correlation between these two scales was established. (c) 2025 Published by Elsevier B.V. on behalf of The Society of Powder Technology Japan. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Particle shape; Gradation; Roughness; Fractal dimension; Interface response; SIZE DISTRIBUTION; SHEAR-STRENGTH; CRITICAL-STATE; BEHAVIOR; DIMENSION; Engineering